ENGLISH LEARNING NEEDS FOR THE MANAGEMENT DEPARTMENT - Rahmatika Kayyis; Dian Pratiwi (Politeknik Negeri Bengkalis, 2022)
The process of using ESP (English for Specific Purposes) to learn English in universities usually does not achieve the best results. One of the contributing factors is the lack of learning programs that are not related to the scientific field they are engaged in. Therefore, it is necessary to formulate a study plan, first analyzing the needs of students to learn English with specific objectives. Therefore, this study aims to find and describe the needs of ESP English learners. This must be done so that the learning of English received is by the scientific field he masters and the field of work he will be involved in. This study used the descriptive qualitative method. The purpose of this study was to determine the need for learning English for the Management study program. The data collection technique used is a questionnaire survey. The data obtained are then classified to identify and describe the needs of students to learn English. The results of this study will be used as a reference for further research, namely syllabus planning and development of ESP English books or teaching materials.